Local delivery of a recombinant adenoassociated vector containing a tumour necrosis factor α antagonist gene in inflammatory arthritis: a phase 1 dose-escalation safety and tolerability study. Issue 8 (4th August 2008) - Mease, P J; Hobbs, K; Chalmers, A; El-Gabalawy, H; Bookman, A; Keystone, E; Furst, D E; Anklesaria, P; Heald, A E
Abstract : Objective: To examine the safety and tolerability of a single intra-articular injection of rAAV2-TNFR:Fc, an adenoassociated virus serotype 2 vector containing the cDNA for the human tumour necrosis factor–immunoglobulin Fc fusion gene (tgAAC94), in subjects with inflammatory arthritis. Methods: In a double-blind, placebo-controlled, phase 1, dose-escalation study, 15 subjects with inflammatory arthritis (14 with rheumatoid arthritis and 1 with ankylosing spondylitis) not receiving tumour necrosis factor α (TNFα) inhibitors with persistent moderate (grade 2) or severe (grade 3) swelling in a target joint due to inflammatory arthritis received a single intra-articular injection of rAAV2-TNFR:Fc at 1×10 10 (n = 5) or 1×10 11 (n = 6) DNase resistant particles per ml joint volume or placebo (n = 4) into a knee (n = 14) or ankle (n = 1). Safety was assessed through adverse event monitoring. As a secondary objective, changes in injected joint tenderness and swelling scores, each measured on a four-point scale, were evaluated. Results: Intra-articular injections of rAAV2-TNFR:Fc were well tolerated with no major safety issues. One event, mild knee pruritis, was considered probably related. Synovial fluid TNFR:Fc protein was not detected (nor expected) at the doses used. At 12 weeks after injection, a two-point decrease in swelling was noted in 2/11 and 2/4 subjects injected with rAAV2-TNFR:Fc and placebo, respectively. Conclusion: A single dose of intra-articular rAAV2-TNFR:Fc appears to be safe and well tolerated in subjects without concurrent systemic TNFα antagonist use. It is thus feasible to proceed with larger trials to further test the safety and efficacy of local TNFR:Fc gene transfer as a therapeutic modality for patients with inflammatory arthritis.